Exploring the Correlation among Employee Performance, Motivation, and Social Life Satisfaction: A Study on Private Commercial Banks in Bangladesh - Shariful Islam, Dr. Mohd. (International Journal of Scientific Research and Management (IJSRM), 2022)
As a key component of economic growth, commercial banks play a pivotal role in the development of trade and industry in a country. At present, 61 scheduled banks are operating in Bangladesh of which 43 are private commercial banks. The performance of these banks’ employees plays a vital role in the economic sustainability and growth of the country. This study focuses on these employees’ performance in the light of their motivation and social life satisfaction.  The data were collected from 204 respondents from the three renowned private commercial banks (Islami Bank Bangladesh Limited, Dutch-Bangla Bank Limited, and Jamuna Bank Limited) through a structured questionnaire. A 5-Point Likert Scale was used to collect primary data and Statistical Package for the Social Science (SPSS) software was used to analyze it. The study revealed that there is a significant positive correlation between employee performance and motivation as well as social life satisfaction. Furthermore, social life satisfaction has the highest positive contribution to performance. Finally, some actionable recommendations were outlined based on the findings of the study.